Wittgenstein's critique of Russell's multiple relation theory of judgement : - Connelly, James R. (Anthem Press, 2021)
This book sets out to adjudicate the scholarly controversy surrounding Wittgenstein's May-June 1913 critique of Russell's multiple-relation theory of judgement. It also aims to familiarize readers with the historical events, textual evidence, letters, working notes and diagrams which are crucial to a correct appreciation of Wittgenstein's criticisms.
Keywords: Wittgenstein, Ludwig, -- 1889-1951.; Russell, Bertrand, -- 1872-1970.; Russell, Bertrand, -- 1872-1970; Wittgenstein, Ludwig, -- 1889-1951; Judgment.; Judgment; Jugement.; Logic.; PHILOSOPHY.; Language.; Electronic books.